Simulation of Dry Reforming of Methane Catalyzed by Iron Hexagonal Mesoporous Silicates (Fe-HMS) Using Aspen HYSYS - Dikwa, Jérôme; Ze Bilo’o, Philemon; Allawadi, Adji (European Journal of Applied Sciences, 2022)
This paper deals with the theoretical study of mesoporous silicates applied to the dry reforming of methane. In order to enhance natural gas and reduce the concentration of carbon dioxide, which is a greenhouse gas in the atmosphere in the same way as methane, the catalytic properties of silicate of the Fe-HMS-n type were used in the simulation of the methane dry reforming reaction on HYSYS. The dry reforming of methane aims to produce syngas, which is an important raw material in the production of fertilizers and resins. Among the Fe-HMS-n silicates used, Fe-HMS-15 provided good catalytic performance for methane dry reforming. A study of the influence of the quantity of iron incorporated in the silicates on the activity was carried out. This led to the conclusion that increasing the iron content improves the catalytic performance of silicates. On the other hand, this performance decreases for high porous volumes. By varying the relative quantity of reactants, the results proved that a molar ratio value greater than unity favors a majority production of dihydrogen due to the decomposition of methane. Conversely, the excess of carbon dioxide leads to the formation of carbon monoxide in a preponderant manner.